FABRICATION OF STYROFOAM FIBERS FOR SOILLESS GROWING MEDIA - Fauzi, Ahmad; Dina, Sharah (Agro Estate, 2025)
The growing interest in urban farming has led to an increased use of non-soil planting media. With land becoming increasingly scarce and expensive, alternative media are being explored for plant cultivation. In parallel, urban waste, particularly styrofoam waste, has emerged as a major issue that demands effective solutions. This paper reports on a continuation of our previous research concerning the development of growing media using styrofoam fibers. Styrofoam waste was collected, cleaned, and processed into fibers using a Rotary Forcespinning apparatus. The resulting fibers were white, durable, long, and had an average diameter of 8 mm. The fibers formed clumps with inter-fiber porosity, and when accumulated in volume, they could be applied as a non-soil planting medium. To be considered a viable planting medium, the styrofoam fiber must be evaluated across several performance parameters, one of which is wettability. Results showed that the water absorption performance of styrofoam fiber was lower compared to that of rockwool and PET fiber media. Future research will focus on improving the water absorption capacity of the styrofoam fiber